Parallel worlds : a journey through creation, higher dimensions, and the future of the cosmos - Kaku, Michio (New York : Doubleday, 2005)
The author presents his theories of a possible parallel universe and maintains that Big Bangs actually created multiple universes making it possible one day to time travel between them.
Includes bibliographical references (p. [403]-405) and index.
Booklist starred.
Library Journal Starred.
Wilson's Senior High School.
Adult
Keywords: Big bang theory; Cosmology; Supergravity; Superstring theories; Big bang theory; Cosmology; Gravitation; Nuclear physics